(untitled) (Nexo Revista Científica, 2020)
The success of micro and small enterprises (MyPE) positively influences the competitiveness and economic growth of a region, so that this research was conducted with the objective of identifying the factors that affect the permanence of the MyPE of the region. tertiary sector in the southeast region of Mexico; case study of the TUXTLAS region. This article details the methodology used in the research using a quantitative approach and the type of descriptive study, for this we proceeded to develop an instrument which was applied to the three main municipalities that make up the Tuxtlas region, considering a population of 4874 MyPE, of which a sample of 253 micro and small businesses was determined, so 65 correspond to the municipality of Catemaco, 145 to San Andrés Tuxtla, and 43 to Santiago Tuxtla. With this research, it was possible to identify that internal control, marketing strategies and strategic planning are key aspects for the permanence of the MyPE in the Southeast region of Mexico.